Model Kecepatan Seismik 1-Dimensi Pada Wilayah Gempa Bumi Tarutung 2022 Mw 5.8 - Resa Idha; Endah P. Sari; Syahrul Humaidi; Andrean V. H Simanjuntak; Umar Muksin (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2023)
On October 1, 2022, an earthquake with a magnitude (M) of 5.8 occurred in the Tarutung region, Indonesia, and was associated with an active fault at a depth of 10 km. The earthquake fault with a dextral mechanism is suitable for the pattern of active fault movement in Sumatra in the Northeast - Southwest direction. A total of 170 aftershocks occurred within a week span with magnitude variations of 1.7 – 4.0. In addition, the Tarutung earthquake was felt by the local people with an intensity of IV-VI MMI and caused 1 fatality, 25 injuries, and around 900 houses damaged. Therefore, this study studies the characteristics of seismicity and damage caused by finding an appropriate 1-Dimensional seismic velocity model. The obtained 1-Dimensional speed model has varying values at a depth of 10 km with a speed of ~5.5 km/s and 30 km with a speed of ~7 km/s. The 1-D velocity model obtained has a convergent and unique solution with an RMS value 1.0. Based on ground motion analysis after relocation, it was found that the high PGA and PGV values were in Tarutung. The PGA results reveal a high percentage value of 10% in Tarutung. This is consistent with the damage data and at the same time confirms that Tarutung is in a seismically active area.